2021
DOI: 10.3390/ijerph18115891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Adaptive Education Program on the Learning, Mental Health and Work Intentions of New Graduate Nurses

Abstract: Health care workers are at a higher risk of psychological distress than ordinary people. Stress affects physical and mental health, and can even produce an intention to leave. The current training for new graduate nurses (NGNs) during this transitional period mostly focuses on the cultivation of professional ability, with less attention to mental health or emotional feelings, and thus there are insufficient structured support strategies. As such, this study explores the effects of intervention through an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Chen et al (2021) describe a programme that provides instruction tailored to the skills, needs and interests of NGRNs, based on their learning styles. This programme addresses three parts: (1) learning care, in which teachers guide the nurse to understand and make good use of their own learning style for better performance; (2) care and monitoring of each new nurse's bio‐psycho‐social health by supervisors and peers; and (3) professional capacity enhancement by combining experiential and clinical learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2021) describe a programme that provides instruction tailored to the skills, needs and interests of NGRNs, based on their learning styles. This programme addresses three parts: (1) learning care, in which teachers guide the nurse to understand and make good use of their own learning style for better performance; (2) care and monitoring of each new nurse's bio‐psycho‐social health by supervisors and peers; and (3) professional capacity enhancement by combining experiential and clinical learning.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions included in the nine studies to retain NGRNs have addressed the development of three competencies, in isolation or combination: core, cross‐cutting and specific (Chen et al, 2021; Hu et al, 2015; Koneri et al, 2021; Krofft & Stuart, 2021; Pillai et al, 2018; Shinners et al, 2021; Torres et al, 2021; Wolford et al, 2019; Zhang et al, 2019). As seen in Table 5, all the studies have addressed the core competencies, five of them the first two, and two studies the three competencies.…”
Section: Resultsmentioning
confidence: 99%
“…The scores were then tallied to obtain the total BSRS-5 score. Patients were further classified into three categories according to their baseline BSRS-5 scores: psychologically healthy (1-5), mild psychological distress (6-9), and moderate to severe psychological distress (≥10) (S. F. Chen et al, 2021).…”
Section: Bsrs-5 Assessmentmentioning
confidence: 99%
“…New nurses need to understand a variety of treatment methods and adverse reaction processing, the management of related drugs, the maintenance of a variety of venous lines, the first-aid for a drug anaphylactic shock, observation and care of bone marrow suppression, prevention and care of radiation inflammation, psychological care for patients with facial defects, improvement in the hospice care for patients at the end stage, implementation of the nurse occupational protection, etc. Nursing postcompetency is based on the cognition and construction method, which reflects the ability of nurses to use various nursing skills, professional knowledge, values, critical thinking, and information as a whole ( 4 ). Multiple studies have shown that a competency-based training system can urge new nurses to improve their professional knowledge and skills, change their working attitudes, etc., and ultimately improve the level of work ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%